Konvergensi Temporal Hari Raya Nyepi dan Idulfitri di Era Digital: Analisis Fenomenologi Komunikasi Agama pada Platform Media Sosial - putu sudibawa; I Wayan Wastawa; Hadianto Ego Gantiano (Dharma Duta, 2026)
This study aims to analyze how the temporal convergence of Nyepi, the Saka New Year 1947, and Eid al-Fitr 1446 AH creates a space for interfaith communication and how religious meanings are negotiated through digital media. This study employs a qualitative approach, with data collected through observations of social media content and interviews with religious leaders, religious social media practitioners, and active digital media users. Observations focused on communication developed across Instagram, TikTok, YouTube, and Twitter/X, particularly the representation of symbols, religious holiday greetings, and interactions among users. The findings show that the temporal proximity of the two religious holidays creates a moment of digital communication that brings together diverse religious identities, symbols, and expressions within the same public space. This process occurs through three main forms: symbolic convergence, reflected in the juxtaposition of Nyepi and Eid al-Fitr symbols; narrative convergence, reflected in the articulation of values such as introspection, peace, self-restraint, purification, forgiveness, and brotherhood; and interactional convergence, manifested through comments, content sharing, discussions, and clarification among users. The study also finds that religious holiday greetings have expanded from ceremonial messages into a medium for meaning negotiation and social communication. Adaptations in language, symbols, and visual representations enable religious messages to maintain their respective spiritual identities while remaining accessible to interfaith audiences. These findings reinforce the Digital Religion perspective, which views digital spaces as social environments where religious practices, identities, and meanings are constructed through interaction, and are consistent with the concept of Network Society, which explains the formation of social relations across boundaries through digital networks. The study concludes that the temporal convergence of Nyepi and Eid al-Fitr is not merely a religious calendar phenomenon but also a communication phenomenon that creates opportunities for dialogue, meaning negotiation, and the strengthening of tolerance and social cohesion within a multireligious society.